PENINGKATAN KEMAMPUAN KERJASAMA ANAK USIA 5-6 TAHUN MELALUI PEMBELAJARAN BERBASIS PROYEK TRADISI SEDEKAH RAME DI TK AZ-ZAHRA KABUPATEN LAHAT - Amanda Zahra, Zalika; Suningsih, Taruni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of cooperation skills in early childhood has become a significant issue as it affects children's social-emotional development and their readiness to interact in learning environments. Therefore, learning approaches that can actively and meaningfully stimulate cooperation are needed. This study aims to improve the cooperation skills of children aged 5–6 years through project-based learning in the Sedekah Rame traditional activity at TK Az-Zahra, Lahat Regency. Sedekah Rame is a cultural tradition of the Lahat community carried out as a form of gratitude by farmers for their harvest, implemented through mutual cooperation, and containing values of togetherness, responsibility, and cooperation that are relevant for early childhood learning. The method used in this study is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which includes the stages of planning, action, observation, and reflection. The research was conducted in two cycles using a collaborative approach between the researcher and the classroom teacher. Data collection techniques included observation, interviews, and documentation, with indicators of cooperation skills consisting of participation, sharing, rule compliance, task implementation, responsibility, and helping one another. The project-based learning was implemented through the stages of identifying real problems, information gathering, planning, implementation, reflection, evaluation, and publication. The results showed an improvement in children's cooperation skills in each cycle. In the pre-cycle stage, the average cooperation ability was 48.89% (Beginning to Develop category), which increased to 65.67% (Developing as Expected) in Cycle I, and further improved to 83.33% (Very Well Developed) in Cycle II. Thus, project-based learning through the Sedekah Rame tradition has been proven effective in improving early childhood cooperation skills while providing contextual and meaningful learning experiences.